Complex analysis - C.I.M.E. Summer School (1973 :|cBressanone, Italy); Gherardelli,F.; SpringerLink (Online service). (Berkeley, Calif. Apress, 2011)
A. Andreotti: Nine lectures on complex analysis.- J.J. Kohn: Propagations of singularities for the Cauchy-Riemann equations.- Yum-Tong Siu: The mixed case of the direct image theorem and its applications.
A. Andreotti: Nine lectures on complex analysis -- J.J. Kohn: Propagations of singularities for the Cauchy-Riemann equations -- Yum-Tong Siu: The mixed case of the direct image theorem and its applications.
Electronic reproduction.
Keywords: Electronic books; Functions of complex variables -- congresses; Mathematical analysis -- ongresses